Knowledge, awareness and impact of coronavirus disease lockdown on training, fitness and personal parameters: A survey of Nigerian athletes - Oke, K. I.; Ogundiran, O. O.; Mbada, C. E.; Ogunkunle, E. (Central European Journal of Sport Sciences and Medicine, 2021)
The study was to assess the knowledge and awareness of COVID-19 pandemic, and the impact of lockdown restrictions on training, fitness and personal parameters of Nigerian athletes. This cross-sectional study recruited 578 elite athletes through an online survey using WhatsApp platform. An adapted questionnaire was used to obtain information on awareness, knowledge and impact of COVID-19 on athletes` characteristics. Descriptive and inferential statistics were used to analyze data. Alpha level was set at p = 0.05. There was high level of awareness (100%) of COVID-19 pandemic among the respondents. The main source of awareness of COVID-19 was social media (68.4%). Some of the respondents (55.9%) had correct knowledge of COVID-19 causative organism. Age was significantly associated with knowledge about cause (X2 = 85.361; p = 0.002) and spread (X2 = 27.715; p = 0.023) of COVID-19 while gender was significantly associated with knowledge about the spread of the virus (X2 = 4.083; p = 0.043). There were significant differences in physical fitness parameters (p < 0.05), eating pattern and body weight measures ( p < 0.05), and general well-being (p = 0.001). Lockdown had negative impacts on hours of daily training, sleeping and eating patterns, physical fitness elements and the general well-being of the respondents.